Determinants of income of extremely poor households in Kota Baru District, Jambi City - Nita Yovita Sari; Yulmardi; Hardiani (Escalate : Economics and Business Journal, 2024)
Extreme poverty in Jambi Province, especially in Kota Baru District with 765 extremely poor households, is a serious challenge. This study analyzes the economic, social, demographic characteristics and income determinants of extremely poor households. Using a quantitative approach, descriptive-explanatory design, primary data from a structured questionnaire on 88 respondents (Cluster Random Sampling from a population of 765 heads of families) and secondary data from BPS and local agencies. Multiple linear regression analysis EViews 12 tested the influence of education, age, dependents, working hours, occupations that passed the classical assumption. The results showed that education (β = 63,817.27, p = 0.000), dependents (β = 45,743.35, p = 0.004), working hours (β = 61,769.63, p = 0.063) had a significant positive effect; age had a significant negative effect (β = -8,326.75, p = 0.003); employment was not significant (p=0.148), explaining 70.4% of the variance in income (R²=0.704). The conclusion recommends vocational training and flexible work policies to alleviate poverty